Cultural and Academic Adaptation Experiences of Timor-Leste Nursing Students in Indonesian Universities: A Qualitative Phenomenological Study - Mulyadi, Eko; Permatasari, Dian; Soares , Domingos; Syarifudin , Muhamad; Sarmento, Julio (Chakra Brahmanda Lentera Institute, 2025)
Background: International education is rapidly expanding, with more students seeking study opportunities abroad. Timor-Leste students in Indonesia often face challenges involving language, academic expectations, and cultural adjustment. However, limited studies have explored their lived experiences. This study aims to explore the cultural and academic adaptation of Timor-Leste students in Indonesian universities. Methods: This study employed a qualitative phenomenological design using Colaizzi’s approach. The population comprised Timor-Leste students currently studying at Indonesian universities. Participants were selected using purposive sampling, with inclusion criteria focusing on students who had studied for at least one academic year, while those with less than six months of experience were excluded. A total of ten participants were included. Data were collected through semi-structured interviews and direct observations. Instruments included an interview guide validated through expert review. Ethical approval number 3470/UN25.8/KEPK/DL/2025. Given that the study was interview-based, its design, conduct, and reporting adhered strictly to the Consolidated Criteria for Reporting Qualitative Research (COREQ) to ensure transparency, reflexivity, and rigor in qualitative interview research. Data were analyzed following Colaizzi’s seven-step method. Results: Thematic analysis revealed three core themes: (1) Cultural and academic shock — students experienced challenges adapting to local customs, social norms, and complex academic language; (2) Differences in learning systems — participants struggled with the shift from teacher-centered to independent learning approaches; and (3) Coping and adaptation strategies — students demonstrated resilience through peer networks, social engagement, and self-adjustment. These themes collectively highlight the dynamic process of cross-cultural adaptation among Timor-Leste students in Indonesian universities. Conclusion: Timor-Leste students in Indonesia encounter significant cultural and academic adaptation challenges. Universities should strengthen inclusive support through structured orientation, language assistance, intercultural mentorship, and psychosocial programs to enhance their academic success and well-being.